Naming animals in Chinese writing - Chang, Han-liang (Sign Systems Studies, 2001)
Naming, according to Sebeok, constihttes the first stage of zoosemiotics. This special but common use of language acrually inaugurates more complicated procedures of human discourse on non-human kingdom, including classification of its members. Because of language's double articulation in sound and sense, as well as the grapheme's pleremic (meaning-full) rather than cenemic (meaning-empty) characteristic (according to Hjelmslev). Chinese script is capable of naming and grouping animals randomly but effectively. This paper attempts to describe the said scriptorial "necessity of naming" (Kripke) in classical Chinese by citing all the creatures, real or fabulous, with a /ma/ (horse) radical.